Solanum aethiopicum L. from the Basilicata region as a source of specialized metabolites with promising anti-obesity effects: phytochemical characterization and in vivo investigation in high fat diet-fed mice - Ponticelli, Maria; Hidalgo-García, Laura; Diez-Echave, Patricia; Vezza, Teresa; Romero, Miguel; Robles-Vera, Iñaki; Duarte, Juan; De Biasio, Filomena; Gorgoglione, Domenico; Lela, Ludovica; Galvez, Julio; Milella, Luigi (Frontiers in Pharmacology, 2023)
Solanum aethiopicum L., commonly known as scarlet eggplant (Solanaceae family) is one of the most traditionally cultivated vegetables in Basilicata, a southern region of Italy. Although multiple uses have been given to this vegetable, data about its anti-obesogenic activity are still limited. This study focuses on testing two different extracts obtained either from the peel or from the whole fruit of the Lucanian S. aethiopicum. Their ability to inhibit certain enzymatic activities was tested in vitro and then, the one that showed the better outcomes was tested on an experimental model of High-Fat Diet (HFD) induced obesity. Spectrophotometric assays demonstrated that the peel extract possessed the highest ability to inhibit the selected enzymatic activities and so, its phytochemical profile was obtained through LC-MS chromatography. The oral administration of this extract (25 mg/kg) to HFD-fed mice reduced body weight gain and improved glucose and lipid metabolism. Similarly, the extract ameliorated the obesityinduced inflammatory status by reducing the expression of pro-inflammatory cytokines in both adipose and hepatic tissues. Interestingly, these effects were associated with the improvement of vascular dysfunction. Lucanian Solanum aethiopicum extract may represent a new strategic approach for managing obesity and its associated diseases.